Characterisation of ocular melanoma with cutaneous melanoma antibodies. Issue 9 (September 1987) - Bomanji, J.; Garner, A.; Prasad, J.; Albert, D. M.; Hungerford, J. L.; Granowska, M.; Britton, K. E.
Abstract : It can be difficult to distinguish between various forms of pale intraocular tumour, and in particular between an amelanotic malignant melanoma, a choroidal haemangioma, and a solitary metastasis. If a monoclonal antibody specific for melanoma could be identified, it might be radiolabelled to provide a scanning technique which could distinguish between an ocular melanoma and a similar lesion. This pilot, in vitro study was undertaken to determine if monoclonal antibody against cutaneous melanoma recognises any antigenic similarity in ocular melanomas. Three cutaneous melanoma MoAbs 225.28S, 376.96S, and 763-24T and a non-specific MoAb HMFG2 were studied. Cell impressions were obtained from fresh ocular malignant melanomas. Standard staining techniques with immunofluorescence were used. MoAb 225.28S, 376.96S, and 763.24T were positive in melanomas with a dominant epithelioid cell type and in those with a dominant spindle cell type. It is concluded that MoAb 225.28S, 376.96S, and 763.24T may be suitable for imaging ocular melanomas after labelling with 123I, 111In, or 99mTc.